PERBEDAAN KOMPRES HANGAT PAYUDARA DAN PIJAT OKSITOSIN TERHADAP KELANCARAN PRODUKSI ASI PADA IBU POST PARTUM DI HARI KE 1-3 DI RS WAVA HUSADA MALANG - Melati Ayu Pratiwi (Health Care Media, 2023)
Mother's milk (ASI) is the best nutrition for babies aged 0-6 months and increases the psychological bond between mother and child. The aim of this study was to determine the difference between warm compresses on the breast and oxytocin massage on the smoothness of milk production for post-partum mothers on days 1-3 at Wava Husada Hospital Malang. This research used a quasi-experimental approach with a non-equivalent control group. The research sample was post-partum mothers on days 1-3 of 60 patients, using a purposive sampling technique. The independent variables are warm compresses and oxytocin massage, and the dependent variable is the smooth production of breast milk. Retrieval of data after passing Etic Clearens, and using a questionnaire. Before being given warm compresses and oxytocin massage both, almost all respondents (93.3%) had less milk production, after being given warm compresses, almost all respondents (80%) had smooth milk production, and after being given oxytocin massage almost all respondents (90%) produced Smooth milk. Mann-Whitney U Test P-value 0.002 <0.05, H0 was rejected. It was concluded that there was a significant difference between warm breast compresses and oxytocin massage on the smooth production of milk in post-partum mothers on Days 1-3. Oxytocin massage has more influence on the smooth production of post-partum mother's milk than warm breast compresses, it is hoped that post-partum mothers can be given oxytocin massage to increase the smoothness of milk production.